PERANAN FAKTOR SUMBER DAYA MANUSIA DALAM MENJAGA KEAMANAN PRODUK PETERNAKAN DARI RESIDU CEMARAN BAHAN KIMIA - Donny Satria, R. Gagak; Trisyono, Andi; Ndaong, Nemay Anggadewi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2015)
In the livestock industry, human resource management would drive the success of production, particularly in an effort to meet the needs of animal protein for the community. At present, the problem of exposure of materials or chemicals in poultry products is increasingly becoming a concern. This study was conducted to determine the association of the human resource with the incidence of chemical residues (for example in this research was deltamethrin) in especially broiler meat. The study was conducted in Sleman, Yogyakarta. Multiple stages sampling method was used to collect 74 samples. Residue analysis performed on 512 specimens that carried out in the Laboratory of Pharmacology of the Faculty of Veterinary Medicine UGM. Survey by interviews and questionnaires conducted to determine the human resource management that applied to the farm. Information from the questionnaire was education level, number of workers, and employment status of workers. Descriptive statistical analysis was used to determine the prevalence of residue and overview of the situation of human resource management on the farm. Logistic regression analysis and the calculation of odds ratios were used to determine the association of predictor factors of the probability of the deltamethrin residues in broiler meat. Linear regression analysis was used to determine the association of factors to predict levels of deltamethrin residues. In conclusion, human resource was important factor in securing animal product, in particular from exposure to chemicals and contaminants. In food safety paradigm, the management should pay attention to the competence of human resource and provide proper salary. Efforts to increase competence through training and continuing education is very important.